UNFPA State of the World Population Report 2011 - Dissanayake, Lakshman (My University, 2011)
The State of the World Population report explores some of achievements, setbacks and paradoxes from the perspective of individuals and describes the obstacles they confront and overcome in trying to build better lives for themselves, their families, communities and nations. Each of the countries featured in this report is seeing in their specific population trends, such as urbanization, longer life expectancies and rapidly expanding working-age populations, not only big challenges but also enormous opportunities to seize these moments and turn them into good news. This report begins with a sampling of young people and a look at what their growing population means in different settings. The chapters that follow then explore ageing populations, migration, the interrelationship among fertility patterns, reproductive health services, gender and the rights of women and girls, the management of vast urban areas and environmental strains. In this report thoughtful, visionary individuals around the world talk about the challenges and opportunities they have in shaping their societies and the global population for this century and beyond. Many of them are young, and conscious of the demographic fact that they will be designing the 21st century world.
Keywords: UNFPA State of the World Population Report 2011